Studi Kasus Penggunaan Video Sebagai Media Pembelajaran Daring Dalam Mata Kuliah Japanese for Business di Era Pandemi - Citra Dewi; Nunik Nur Rahmi Fauzah (IZUMI, 2022)
In the covid 19 pandemic era, education in Indonesia is appliying an online learning system. The use of technology and computer-based applications is inevitable. Teachers are faced with the use of applications such as Zoom, G Classroom, Screenomatic, Canva, Prezi, and others. The use of these applications is constructive in the knowledge transfer process. However, the use of supporting media in online learning also plays an important role. Because in practice, the use of learning media will greatly help the learning process. One of them is by using video media. Video is a multimedia-based learning media. In the video, learners can listen to the material through audio-visual which can help optimize the function of the five senses and make it easier for learners to understand the content of the material presented. This research will use videos from a Youtube channel. One course that requires videos as learning media is Japanese for Business, which is given to 3rd year 6th-semester students for 4 meetings with various themes. In this course, students are taught Japanese conversation for business. The difficulties faced in online learning are the lack of time for practice and limited language use situations. Moreover, the pandemic period has also affected the company's work system, so it is necessary to deliver material about the work system. Such as presentations and meetings through zoom as well as other situations that might occur in the online work system. Based on this background, it can be concluded that the purpose of this study is to find out how teaching in Japanese for Business course through the use of video media in the pandemic era. The method used is a mixed method. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor